Anti-crack nickel-based superalloy as well as preparation method and application thereof

By using rare earth oxide passivation of aluminum and Ni-B master alloying processes, combined with pulsed electroslag remelting and multi-directional forging, the problem of grain boundary cracking in nickel-based superalloys during high-temperature service was solved, improving their crack resistance and service stability.

CN120796781AActive Publication Date: 2025-10-17上海一郎合金材料有限公司

Patent Information

Application Number
CN202511240164.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-01
Publication Date
2025-10-17
Estimated Expiration
2045-09-01

AI Technical Summary

Technical Problem

Nickel-based superalloys are prone to grain boundary cracking during high-temperature service, which leads to a decrease in fatigue strength and yield strength, seriously affecting the service life of components.

Method used

Aluminum is passivated with rare earth oxides to form a Y2O3 passivation layer. Boron segregation is avoided by using a Ni-B master alloy preparation process. Combined with pulse electroslag remelting and multi-directional forging processes, the grains are refined, and the grain boundary bonding energy and crack resistance are improved.

Benefits of technology

It significantly reduces the crack propagation rate under high-temperature cyclic loading, improves the long-term service stability of the alloy in the coupled environment of oxidation and hot corrosion, extends the service life of components, and reduces the risk of cracking during cold rolling and cold drawing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses an anti-crack nickel-based superalloy and a preparation method and application thereof, and belongs to the technical field of nickel-based alloys. The anti-crack nickel-based superalloy comprises, by mass, 12%-18% of Cr, 10%-20% of Ni, 10%-20% of Ni and the balance Ni; 8%-15% of Co; 3 to 6 percent of Mo; 2 to 4 percent of W; 1 to 3 percent of Al; 2 to 4 percent of Ti; 0.5 to 2 percent of Ru; 0.3%-1% of Y; b: 0.002 to 0.01% of the total weight of the raw materials; and the balance of Ni and inevitable impurities. According to the invention, aluminum is passivated by the rare earth oxide to form a Y2O3 passivation layer, so that the precipitation of a low-melting-point phase is effectively inhibited, the crack propagation rate under high-temperature cyclic load is remarkably reduced, the grain boundary binding energy is optimized, and the long-term service stability of the alloy in an oxidation-hot corrosion coupling environment is improved. Through a Ni-B intermediate alloy preparation process and carbon thermal reduction and liquid filtration technologies, boron element segregation and brittle boride formation are avoided, a grain boundary stress concentration source is eliminated, and boron elements are uniformly distributed on a matrix, so that the intergranular fracture tendency is inhibited under high-temperature and high-stress conditions, and the service life of the alloy is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of nickel-based alloys, in particular to an anti-cracking nickel-based superalloy and a preparation method and application thereof. BACKGROUND

[0002] As the core material of the hot end components of the aero-engine and gas turbine, the nickel-based superalloy needs to maintain excellent microstructure stability, fatigue resistance and corrosion resistance under high temperature (950-1050℃) and complex stress environment. However, during long-term high-temperature service, the fatigue strength, yield strength and creep resistance of the alloy will decrease significantly, and the grain boundary cracking is one of the main failure modes.

[0003] When the conventional aluminum powder is added, the Al2O3 passivation layer formed on the surface has low density, and the oxygen diffusion and penetration during high-temperature smelting leads to the precipitation of low-melting-point phases at the grain boundaries, which significantly weakens the grain boundary binding energy, causing the crack propagation rate to increase sharply under high-temperature cyclic load when the alloy is long-term served in the oxidation-thermal corrosion coupled environment (such as the combustion chamber of the aero-engine), which seriously restricts the service life of the components.

[0004] When boron powder is directly added, it is easy to float and agglomerate due to its low density, and the impurities of B2O3 on the surface react with the base elements to generate brittle eutectic phases with a melting point lower than 900℃, and the coarse borides formed by the segregation of the eutectic phases at the grain boundaries become stress concentration sources. Under high-temperature and high-stress working conditions, cracks rapidly propagate along the brittle borides to cause intergranular fracture, resulting in early failure of the components.

[0005] Therefore, the skilled in the art is committed to developing an anti-cracking nickel-based superalloy and a preparation method and application thereof to solve the above problems. SUMMARY

[0006] In view of the above defects of the prior art, the technical problem to be solved by the present application is to improve the anti-cracking ability of the nickel-based superalloy.

[0007] To achieve the above-mentioned purpose, the present application provides an anti-cracking nickel-based superalloy, which comprises the following components in mass percentage: Cr: 12-18%; Co: 8-15%; Mo: 3-6%; W: 2-4%; Al: 1-3%; Ti: 2-4%; Ru: 0.5-2%; Y: 0.3-1%; B: 0.002-0.01%; the balance being Ni and unavoidable impurities. Among them, Al is treated by Y2O3 passivation; B exists in the form of Ni-B intermediate alloy.

[0008] A preparation method of the anti-cracking nickel-based superalloy, comprising the following steps: S1. Pretreatment of aluminum; Mixing aluminum powder and yttrium oxide powder, sintering under argon protection, and grinding to obtain passivated aluminum powder; S2. Preparing Ni-B intermediate alloy; The nickel oxide powder is immersed in a boron-containing solution and stirred, and then dried in high-temperature air to obtain pre-coated nickel oxide powder; The boron anhydride powder and the pre-coated nickel oxide powder are vacuum-dried, mixed after sieving, added with polyvinyl alcohol binder, cold isostatic pressed, and heated to generate liquid Ni(BO2)2 under argon protection; After pre-reducing the liquid Ni(BO2)2 with carbon powder at 1350℃ for 30 min, NiB is generated by constant temperature reaction at 1550-1600℃; slowly cooled to 1200-1300℃ and kept for a while, and then filtered to intercept inclusions; The NiB intermediate alloy is poured to obtain NiB intermediate alloy powder; S3. Vacuum induction melting and degassing treatment; The dried nickel, chromium, cobalt, molybdenum, tungsten, titanium and ruthenium powders are added into a vacuum induction furnace, vacuum-extracted, heated to 1950-2000℃, and then cooled to 1550-1600℃ for constant temperature melting; high-purity argon is introduced for degassing treatment; After being cooled to 1450-1500℃, the passivated aluminum powder is added; and the Ni-B intermediate alloy powder is added in batches; When the temperature is reduced to 1400-1450℃, the furnace is poured into a water-cooled copper mold to obtain an ingot; S4. Pulse electroslag remelting; The preheated and dehydrated ternary slag system CaF2-Al2O3-CaO is loaded into a crystallizer by using an electroslag remelting furnace; the furnace body is vacuum-extracted and high-purity argon is introduced before melting, and the crystallizer cooling water system is started synchronously; the ingot is put into the molten pool and intermittently pulsed; S5. Open-die forging; The ingot is heated to 1150-1200℃ and kept for a while by using a fast forging machine, and then multi-directional forging process of axial and radial alternating deformation is adopted, and then air-cooled to room temperature; S6. Cold rolling and cold drawing; After cold rolling, the blank is immediately annealed, the surface of the blank is uniformly sprayed with high-temperature resistant lubricant, and after the lubricating layer is solidified, cold drawing is carried out to obtain a finished product; the finished product is polished in an electrolyte; S7. Annealing by heat treatment; After the solid solution treatment, high-pressure nitrogen gas with a pressure of 1.2 MPa is introduced to rapidly cool to 300℃ at a speed of 50-100℃ / min; the aging treatment is carried out, and then the furnace is cooled and air-cooled to obtain the crack-resistant nickel-based high-temperature alloy.

[0009] In the preferred embodiment of the present application, S1 is specifically: the aluminum powder is mixed with yttrium oxide powder, sintered at 380-400℃ for 1-2h under argon protection, and ground into passivated aluminum powder with a particle size of ≤50μm.

[0010] In another preferred embodiment of the present application, S2 is specifically: completely immerging the nickel oxide powder into a boron-containing solution and stirring, oxidizing and drying in high-temperature air to form a Ni-B-O coating layer on the surface, thereby obtaining pre-coated nickel oxide powder; Vacuum drying the boron anhydride powder and the pre-coated nickel oxide powder to remove adsorbed water, and sieving to a particle size of ≤50 μm; Mixing B2O3 and NiO in a molar ratio of 1:1-1.2, adding polyvinyl alcohol binder, cold isostatic pressing into a cylindrical block, heating to 950-1000 °C under argon protection, and keeping the temperature for 1-1.5 h to react to form liquid Ni(BO2)2; Loading the liquid Ni(BO2)2 and carbon powder in a vacuum induction furnace in a molar ratio of 1:2.4-2.8, passing argon gas; pre-reducing at 1350 °C for 30 min, and then keeping the temperature constant at 1550-1600 °C for 40-50 min to generate NiB through carbothermic reduction; Slowly cooling to 1200-1300 °C and keeping the temperature, and filtering to intercept inclusions; Pouring into a water-cooled copper mold, controlling the cooling rate at 50-100 °C / s, and obtaining NiB intermediate alloy, and grinding the NiB intermediate alloy powder to a particle size of ≤50 μm.

[0011] In another preferred embodiment of the present application, S3 is specifically: controlling the particle size of nickel, chromium, cobalt, molybdenum, tungsten, titanium, and ruthenium powders at 50-150 μm, pre-vacuum drying, adding the powders into a vacuum induction furnace in the order of bottom layer high-melting-point metal W, Mo, middle layer Ni, Co, Cr, and top layer low-melting-point metal Ti, Ru, first using a mechanical pump to pump, and then using a molecular pump to pump to ≤5×10 -3 Pa, heating to 1950-2000 °C at a speed of 10-15 °C / min, keeping the temperature for 30-40 min to completely dissolve the refractory metal, cooling to 1550-1600 °C, and keeping the temperature constant for 2-2.5 h for smelting; Passing high-purity argon gas at a flow rate of 5-10 L / min for 20-30 min for degassing treatment at 50-80 Pa; After cooling to 1450-1500 °C, adding passivated aluminum powder through a vacuum chamber secondary feeding device; adding Ni-B intermediate alloy powder in 2-3 times with an interval of 3-5 min each time; When the temperature drops to 1400-1450 °C, pouring into a water-cooled copper mold to obtain an ingot at a pouring speed of 3-5 kg / min; and taking out the ingot after cooling under argon protection.

[0012] In another preferred embodiment of the present application, S4 is specifically: using an electroslag remelting furnace, preheating and dehydrating the ternary slag system CaF2-Al2O3-CaO to make the water content of the slag ≤0.05%, and loading into the crystallizer; before smelting, vacuumizing the furnace body to ≤10 Pa, continuously introducing high-purity argon into the furnace until the oxygen content in the furnace is ≤50 ppm, synchronously starting the crystallizer cooling water system, keeping the temperature difference between the inlet and outlet of the cooling water ≤5 ℃, and preventing local overheating; putting the ingot into the molten pool, controlling the voltage 40-50 V, the current 2000-3000 A, and intermittent pulse.

[0013] In another preferred embodiment of the present application, S5 is specifically: using a quick forging machine to heat the ingot to 1150-1200 ℃ and keeping for 1.5-2 h, using a multi-directional forging process of axial and radial alternating deformation, and finally forging at 900-950 ℃, and then air cooling to room temperature.

[0014] In another preferred embodiment of the present application, S6 is specifically: using a two-roller cold rolling machine and a chain type cold drawing machine to work cooperatively, first cold rolling and then cold drawing: immediately transferring the cold-rolled blank to an argon-protected annealing furnace, keeping at 750-800 ℃, slowly cooling at a rate of ≤30 ℃ / min, and then air cooling, uniformly spraying a high-temperature lubricant on the surface of the blank to a thickness of 5-10 μm, and after the lubricating layer is solidified, carrying out cold drawing to obtain a finished product; polishing treatment in an electrolyte.

[0015] In another preferred embodiment of the present application, S7 is specifically: solid solution treatment in a box-type vacuum furnace at 1080-1120 ℃ in an argon atmosphere; after the solid solution treatment is completed, introducing 1.2 MPa high-pressure nitrogen to rapidly cool to 300 ℃ at a rate of 50-100 ℃ / min; aging treatment when the temperature is raised to 750-800 ℃, air cooling after furnace cooling, and obtaining the anti-cracking nickel-based high-temperature alloy.

[0016] The application of the anti-cracking nickel-based high-temperature alloy in the preparation of an aero-engine hot-end component or a gas turbine hot-end component.

[0017] The method provided by the present application has the following technical effects: 1. The present application forms a Y2O3 passivation layer through passivation treatment of aluminum by rare earth oxides, effectively inhibits the precipitation of low-melting-point phases, significantly reduces the crack propagation rate under high-temperature cyclic load, optimizes the grain boundary bonding energy, and improves the long-term service stability of the alloy in an oxidation-thermal corrosion coupled environment (such as an aero-engine hot-end component).

[0018] 2. The present application avoids boron segregation and the formation of brittle borides through the Ni-B intermediate alloy preparation process, eliminates the grain boundary stress concentration source, makes the boron element uniformly distributed in the matrix, thereby inhibiting the tendency of intergranular fracture under high-temperature and high-stress conditions (such as 850 ℃ / 780 MPa), and prolonging the service life of the alloy.

[0019] 3、The present application combines pulse electroslag remelting and multi-directional forging process, refines grains and eliminates solidification defects, greatly reduces the cracking risk in the cold rolling and cold drawing process of seamless pipe, and improves the forming qualified rate of complex components (such as gas turbine guide pipes).

[0020] The concept, specific structure and technical effects of the present application will be further described below to fully understand the purposes, features and effects of the present application. DETAILED DESCRIPTION

[0021] The embodiments of the present application will be described below through specific examples, and those skilled in the art can easily understand other advantages and effects of the present application from the disclosure. The present application can also be implemented or applied through other different embodiments, and various modifications or changes can be made to the details in the specification based on different views and applications without departing from the spirit of the present application. It should be noted that the following examples and features in the examples can be combined with each other without conflict.

[0022] Example 1: The present example provides a crack-resistant nickel-based superalloy, which comprises the following components by mass percentage: Cr: 18%; Co: 15%; Mo: 6%; W: 4%; Al: 3%; Ti: 4%; Ru: 2%; Y: 1%; B: 0.01%; The balance is Ni and unavoidable impurities.

[0023] Among them, Al is passivated by Y2O3; B exists in the form of Ni-B intermediate alloy.

[0024] The specific preparation method comprises the following steps: S1. Pretreatment of aluminum - coating passivation + rare earth modification; Mix aluminum powder (particle size ≤50 μm) with yttrium oxide powder (particle size ≤20 μm), sinter at 400°C for 2h under argon protection, and grind to passivated aluminum powder with particle size ≤50 μm; S2. Preparation of Ni-B intermediate alloy; Completely immerse nickel oxide powder (NiO) into a boron-containing solution (0.5 mol / L NaBH4 + 0.2 mol / L citric acid), stir at 60°C for 30 min, oxidize in air at 250°C for 40 min to form a Ni-B-O coating layer on the surface, and obtain pre-coated nickel oxide powder; Boric anhydride powder (B2O3) and pre-coated nickel oxide powder were vacuum dried at 150℃ for 4h to remove adsorbed water, sieved to a particle size of ≤50μm, and the reaction contact area was increased; B2O3 and NiO were mixed in a molar ratio of 1:1.2, 0.5% of the total amount of polyvinyl alcohol binder was added, cold isostatic pressing (300MPa) was performed to form a Φ50×50mm cylindrical block, and the block was heated to 1000℃ under argon protection, and held for 1.5h to generate liquid Ni(BO2)2 by reaction; The liquid Ni(BO2)2 and carbon powder were loaded into a vacuum induction furnace (≤5×10 -3 Pa) in a molar ratio of 1:2.8, argon gas (5L / min) was passed, and the temperature was held at 1350℃ for 30min (pre-reduction) and at 1600℃ for 50min to generate NiB by carbothermic reduction; The temperature was slowly cooled to 1300℃ at a rate of 5℃ / min, and the temperature was held for 30min to promote uniform precipitation of the NiB phase. Zirconia porous ceramic filter screens (pore size 1.0mm) were used for filtration to intercept inclusions; The NiB intermediate alloy was poured into a water-cooled copper mold, and the cooling rate was controlled at 100℃ / s to obtain a NiB intermediate alloy with a particle size of ≤50μm; S3. Vacuum induction melting and degassing treatment; The particle size of nickel, chromium, cobalt, molybdenum, tungsten, titanium, and ruthenium powders was controlled at 150μm, and the powders were pre-dried in a vacuum drying oven at 120℃ for 4h. The powders were added to a 2000℃ vacuum induction furnace (vacuum degree ≤10 -3 Pa) in the order of bottom layer high melting point metal W, Mo, middle layer Ni, Co, Cr, and top layer low melting point metal Ti, Ru. The mechanical pump was first used to pump to 10Pa, and then the molecular pump was used to pump to ≤5×10 -3 Pa. The temperature was raised to 2000℃ at a rate of 15℃ / min, and the temperature was held for 40min to completely dissolve the refractory metals (W, Mo). The temperature was then lowered to 1600℃, and the temperature was held for 2.5h for melting; Argon gas with a purity of 99.9% was introduced at a flow rate of 10L / min, and the degassing treatment was performed at 80Pa for 30min; After the temperature was lowered to 1500℃, aluminum powder was added through the vacuum chamber secondary feeding device. The Ni-B intermediate alloy powder was added in three portions with an interval of 5min between each addition; When the temperature was lowered to 1450℃, the furnace was tilted to pour the ingot into a water-cooled copper mold at a pouring speed of 5kg / min to avoid oxidation caused by turbulent flow; The ingot was cooled to 300℃ under argon protection before being removed from the furnace to reduce thermal stress cracks; S4. Pulse electroslag remelting; The CaF2-Al2O3-CaO (mass ratio 55:30:15) ternary slag system is preheated and dehydrated at 800°C for more than 4 hours to make the water content of the slag ≤0.05%, and is loaded into the crystallizer; before smelting, the furnace body is vacuumed to ≤10 Pa, then high-purity argon is continuously introduced until the oxygen content in the furnace is ≤50 ppm, the crystallizer cooling water system is started synchronously, the flow rate is controlled to be 12 m / h, and the temperature difference between the inlet and outlet of the cooling water is kept ≤5°C to prevent local overheating; a 45V voltage and 2500A current are used to establish a molten pool in the arc starting stage, the ingot is put in, and after the steady state is entered, the voltage is controlled to be 50V and the current is controlled to be 3000A, the pulse is turned on for 30s every 5min of smelting, and the pulse power parameters are frequency 120Hz, pulse width 400ms, and current peak value 450A; S5. Upsetting forging; Using a 1000-ton fast forging machine, the ingot is heated to 1200°C and kept for 2 hours, a multi-directional forging process (axial upsetting → radial elongation → second axial upsetting → radial shaping) of alternating axial and radial deformation is adopted, the total forging ratio is ensured to be ≥8, the final forging temperature is 950°C, and then air cooling is performed to room temperature; S6. Cold rolling and cold drawing; Using a two-roll cold rolling machine (reduction ratio ≤18%) and a chain type cold drawing machine (elongation coefficient ≤2.0) to work cooperatively, the cold rolling is performed first and then the cold drawing is performed: after the cold rolling, the blank is immediately transferred to an argon protection annealing furnace, is slowly cooled to 600°C at a rate of ≤30°C / min after being kept at 800°C for 2h, and is then air cooled, the surface of the blank is uniformly sprayed with a high-temperature resistant lubricant (WS2 powder, at least below 400°C, the lubricating properties of WS2 are basically not affected) to a thickness of 10μm, the cold drawing is performed after the lubricating layer is solidified, and a finished product (seamless steel pipe) with an outer diameter of φ50mm and a wall thickness of 5mm is obtained; after being confirmed to be defect-free by eddy current testing, the finished product is placed in a perchloric acid-ethanol electrolyte (volume ratio 1:9) at -10±2°C, and is subjected to surface treatment by electrolytic polishing for 8min with a lead plate as a cathode and a voltage of 18V; S7. Heat treatment annealing; In a box-type vacuum furnace (vacuum degree ≤10 -2 Pa), solid solution treatment is performed at 1120°C in an argon atmosphere for 2h; immediately after the solid solution treatment, 1.2MPa high-pressure nitrogen gas is introduced to rapidly cool to 300°C at a rate of 100°C / min; then, aging treatment is performed at 800°C for 8h, the furnace is cooled to 500°C, and then air cooling is performed, to obtain the anti-cracking nickel-based superalloy.

[0025] Embodiment 2: The embodiment provides an anti-cracking nickel-based superalloy, which contains the following components in percentage by mass: Cr: 12%; Co: 8%; Mo: 3%; W: 2%; Al: 1%; Ti: 2%; Ru: 0.5%; Y: 0.3%; B: 0.002%; The balance is Ni and inevitable impurities.

[0026] Wherein, the Al is passivated by Y2O3; and the B exists in the form of Ni-B intermediate alloy.

[0027] The specific preparation method comprises the following steps: S1. Pretreatment of aluminum - coating passivation + rare earth modification; Mixing aluminum powder (particle size ≤ 50 μm) with yttrium oxide powder (particle size ≤ 20 μm), sintering at 380 ℃ for 1 h under argon protection, and grinding to passivated aluminum powder with particle size ≤ 50 μm; S2. Preparation of Ni-B intermediate alloy; Completely immerse nickel oxide powder (NiO) into a boron-containing solution (0.5 mol / L NaBH4 + 0.2 mol / L citric acid), stir at 60 ℃ for 30 min, oxidize in air at 250 ℃ for 40 min to form a Ni-B-O coating layer on the surface, and obtain pre-coated nickel oxide powder; Vacuum dry boron anhydride powder (B2O3) and pre-coated nickel oxide powder at 150 ℃ for 4 h to remove adsorbed water, sieve to particle size ≤ 50 μm, and improve the reaction contact area; Mix B2O3 and NiO in a molar ratio of 1:1, add 0.5% of polyvinyl alcohol binder based on the total amount of the two, cold isostatic pressing (300 MPa) into a Φ50×50 mm cylindrical block, heat to 950 ℃ under argon protection, and keep for 1 h to react to generate liquid Ni(BO2)2; Load liquid Ni(BO2)2 and carbon powder in a vacuum induction furnace (≤5×10 -3 Pa) in a molar ratio of 1:2.4, pass argon gas (5 L / min), keep at 1350 ℃ for 30 min (pre-reduction), and keep at 1550 ℃ for 40 min to generate NiB through carbothermic reduction; Slowly cool to 1200 ℃ at a rate of 5 ℃ / min, keep for 30 min to promote uniform precipitation of NiB phase, filter using a zirconia porous ceramic filter screen (pore size 0.5 mm) to intercept inclusions; Pour into a water-cooled copper mold, control the cooling rate at 50 ℃ / s, obtain NiB intermediate alloy, and grind to NiB intermediate alloy powder with particle size ≤ 50 μm; S3. Vacuum induction melting and degassing treatment; The particle size of nickel, chromium, cobalt, molybdenum, tungsten, titanium, ruthenium powder is controlled at 50 μm, and is pre-dehydrated in a 120°C vacuum drying box for 4h, and is added into a 2000°C vacuum induction furnace (vacuum degree ≤10 -3 Pa) in the order of bottom layer high melting point metal W, Mo, middle layer Ni, Co, Cr, and top layer low melting point metal Ti, Ru, is first mechanically pumped to 10 Pa, and then is pumped to ≤5×10 -3 Pa by a molecular pump, is heated to 1950°C at a speed of 10°C / min, is kept for 30 min to make the refractory metal (W, Mo) completely dissolved, is cooled to 1550°C, and is kept for 2h for smelting; The argon gas with a purity of 99.9% is introduced at a flow rate of 5 L / min, and is degassed at 50 Pa for 20 min; After being cooled to 1450°C, the passivated aluminum powder is added through a vacuum chamber secondary feeding device; the Ni-B intermediate alloy powder is added in two times with an interval of 3 min; When the temperature is reduced to 1400°C, the furnace is tilted to pour into a water-cooled copper mold to obtain an ingot, and the pouring speed is 3 kg / min to avoid oxidation caused by turbulent flow; The ingot is cooled to 300°C under argon protection, and is discharged to reduce thermal stress cracks; S4. Pulse electroslag remelting; The ternary slag system CaF2-Al2O3-CaO (mass ratio 55:30:15) is preheated and dehydrated at 800°C for more than 4h to make the water content of the slag ≤0.05%, and is loaded into a crystallizer; before smelting, the furnace body is pumped to ≤10 Pa, and then high-purity argon is continuously introduced until the oxygen content in the furnace is ≤50 ppm, the crystallizer cooling water system is started synchronously, the flow rate is controlled at 12 m / h, and the temperature difference between the inlet and outlet of the cooling water is kept ≤5°C to prevent local overheating; a 45V voltage and a 2500A current are used to establish a molten pool in the arc starting stage, the ingot is put in, and after the steady state is entered, the voltage is controlled at 40V and the current is controlled at 2000A, the pulse is opened for 30s every 5 min of smelting, and the pulse power parameters are frequency 120Hz, pulse width 400ms, and current peak value 450A; S5. Blooming forging; The 1000-ton fast forging machine is used to heat the ingot to 1150°C and keep for 1.5h, the multi-directional forging process (axial upsetting → radial elongation → second axial upsetting → radial shaping) of alternating axial and radial deformation is adopted, the total forging ratio is ensured to be ≥8, the final forging temperature is 900°C, and then air cooling is performed to room temperature; S6. Cold rolling and cold drawing; A two-roller cold rolling mill (reduction ratio ≤18%) and a chain-type cold drawing machine (elongation coefficient ≤2.0) are used in cooperation to first cold roll and then cold draw: the cold-rolled blank is immediately transferred to an argon-protected annealing furnace, and is slowly cooled at a rate of ≤30℃ / min to 600℃ after being kept at 750℃ for 2h and then air-cooled, the surface of the blank is uniformly sprayed with a high-temperature-resistant lubricant (WS2 powder) to a thickness of 5μm, and after the lubricating layer is solidified, cold drawing is performed to obtain a finished product (seamless steel pipe) with an outer diameter of φ40mm and a wall thickness of 3mm; after being confirmed to be free of defects by eddy current testing, the product is placed in a high-chloric acid-ethanol electrolyte (volume ratio 1:9) at -10±2℃, and is subjected to surface treatment by electrolytic polishing for 8min at a voltage of 18V with a lead plate as the cathode; S7. heat treatment annealing; In a box-type vacuum furnace (vacuum degree ≤10 -2 Pa), solution treatment is performed at 1090℃ in an argon atmosphere for 2h; immediately after the solution treatment, high-pressure nitrogen gas at 1.2MPa is introduced to rapidly cool to 300℃ at a rate of 50℃ / min; then, aging treatment is performed at 780℃ for 8h, and the furnace is cooled to 500℃ and then air-cooled, to obtain a crack-resistant nickel-based high-temperature alloy.

[0028] Embodiment 3: This embodiment provides a crack-resistant nickel-based high-temperature alloy, which comprises the following components in terms of mass percentage: Cr: 15%; Co: 12%; Mo: 5%; W: 3%; Al: 2%; Ti: 3%; Ru: 0.9%; Y: 0.6%; B: 0.008%; the balance being Ni and unavoidable impurities.

[0029] Among them, Al is subjected to Y2O3 passivation treatment; B exists in the form of Ni-B intermediate alloy.

[0030] The specific preparation method comprises the following steps: S1. Pretreatment of aluminum - coating passivation + rare earth modification; Aluminum powder (particle size ≤50μm) is mixed with yttrium oxide powder (particle size ≤20μm), and is sintered at 385℃ for 1.5h under argon protection, and is ground to a passivated aluminum powder with a particle size of ≤50μm; S2. Preparation of Ni-B intermediate alloy; The nickel oxide powder (NiO) is completely immersed in a boron-containing solution (0.5 mol / L NaBH4+0.2 mol / L citric acid), stirred at 60°C for 30 min, oxidized in air at 250°C for 40 min to form a Ni-B-O coating layer on the surface, and pre-coated nickel oxide powder is obtained; The boron anhydride powder (B2O3) and the pre-coated nickel oxide powder are vacuum dried at 150°C for 4 h to remove adsorbed water, and sieved to a particle size of ≤50 μm to increase the reaction contact area; The B2O3 and the NiO are mixed in a molar ratio of 1:1.1, 0.5% of polyvinyl alcohol binder is added based on the total amount of the two, cold isostatic pressing (300 MPa) is performed to form a Φ50×50 mm cylindrical block, the block is heated to 980°C under argon protection, and heat preservation is performed for 1.5 h to react to generate liquid Ni(BO2)2; The liquid Ni(BO2)2 and carbon powder are loaded into a vacuum induction furnace (≤5×10 -3 Pa) in a molar ratio of 1:2.5, argon gas (5 L / min) is introduced, heat preservation is performed at 1350°C for 30 min (pre-reduction), and carbon thermal reduction reaction is performed at 1580°C for 48 min to generate NiB; The temperature is slowly cooled to 1280°C at a rate of 5°C / min, heat preservation is performed for 30 min to promote uniform precipitation of the NiB phase, and a zirconia porous ceramic filter screen (pore size 0.8 mm) is used for filtration to intercept inclusions; The mixture is poured into a water-cooled copper mold, the cooling rate is controlled to be 80°C / s, and the NiB intermediate alloy is obtained, and the NiB intermediate alloy powder with a particle size of ≤50 μm is obtained by grinding; S3. Vacuum induction melting and degassing treatment; The particle size of the nickel, chromium, cobalt, molybdenum, tungsten, titanium, and ruthenium powders is controlled to be 100 μm, the powders are pre-dehydrated in a vacuum drying oven at 120°C for 4 h, the powders are added into a 2000°C vacuum induction furnace (vacuum degree ≤10 -3 Pa) in the order of bottom layer high melting point metal W, Mo, middle layer Ni, Co, Cr, and top layer low melting point metal Ti, Ru, the mechanical pump is first used to pump to 10 Pa, and then the molecular pump is used to pump to ≤5×10 -3 Pa, the temperature is increased to 1970°C at a rate of 12°C / min, heat preservation is performed for 34 min to completely dissolve the refractory metals (W, Mo), the temperature is decreased to 1590°C, and heat preservation melting is performed for 2 h; The argon gas with a purity of 99.9% is introduced at a flow rate of 8 L / min, and the degassing treatment is performed at 70 Pa for 28 min; After the temperature is decreased to 1480°C, the passivated aluminum powder is added through a vacuum chamber secondary feeding device; the Ni-B intermediate alloy powder is added in three times with an interval of 4 min each time; When the temperature is decreased to 1420°C, the furnace is tilted to pour the mixture into a water-cooled copper mold to obtain an ingot, the pouring speed is 4 kg / min to avoid oxidation caused by turbulent flow; The ingot is discharged after cooling to 300℃ under argon protection to reduce thermal stress cracks; S4. Pulse electroslag remelting; A ternary slag system CaF2-Al2O3-CaO (mass ratio 55:30:15) is preheated and dehydrated at 800℃ for more than 4h in an electroslag remelting furnace to make the water content of the slag ≤0.05%, and is loaded into the crystallizer; before smelting, the furnace body is vacuumed to ≤10 Pa, then high-purity argon is continuously introduced into the furnace until the oxygen content in the furnace is ≤50 ppm, the crystallizer cooling water system is started synchronously, the flow rate is controlled at 12 m / h, and the temperature difference between the inlet and outlet of the cooling water is kept ≤5℃ to prevent local overheating; a 45V voltage and 2500A current are used to establish the molten pool in the arc striking stage, the ingot is put in, and after the steady state is entered, the voltage is controlled at 47V and the current is controlled at 2200A, the pulse is turned on for 30s every 5min of smelting, and the pulse power parameters are frequency 120Hz, pulse width 400ms, and current peak value 450A; S5. Upsetting forging; A 1000-ton fast forging machine is used to heat the ingot to 1180℃ and keep it for 1.5h, a multi-directional forging process (axial upsetting → radial elongation → second axial upsetting → radial shaping) of alternating axial and radial deformation is adopted to ensure that the total forging ratio is ≥8, and the final forging temperature is 920℃, followed by air cooling to room temperature; S6. Cold rolling and cold drawing; A two-roll cold rolling mill (reduction ratio ≤18%) and a chain type cold drawing machine (elongation coefficient ≤2.0) are used to work cooperatively, and the cold rolling is followed by cold drawing: after cold rolling, the blank is immediately transferred to an argon protection annealing furnace, is kept at 770℃ for 2h, is slowly cooled to 600℃ at a rate of ≤30℃ / min, and is then air cooled; the surface of the blank is uniformly sprayed with a high-temperature resistant lubricant (WS2 powder) to a thickness of 8μm, and after the lubricating layer is solidified, cold drawing is carried out to obtain a finished product (seamless steel pipe) with an outer diameter of φ30mm and a wall thickness of 3mm; after being confirmed to be defect-free by eddy current testing, the finished product is placed in a perchloric acid-ethanol electrolyte (volume ratio 1:9) at -10±2℃, and is subjected to surface treatment by electrolytic polishing for 8min with a lead plate as the cathode and a voltage of 18V; S7. Heat treatment annealing; It is carried out in a box-type vacuum furnace (vacuum degree ≤10 -2 Pa) under an argon atmosphere at 1110℃ for 2h; immediately after solid solution treatment, 1.2MPa high-pressure nitrogen gas is introduced to rapidly cool to 300℃ at a rate of 80℃ / min; then, aging treatment is carried out at 770℃ for 8h, the furnace is cooled to 500℃, and then air cooling is carried out to obtain the crack-resistant nickel-based superalloy.

[0031] Comparative Example 1: The difference from Example 3 is that Al is not subjected to Y2O3 passivation treatment, but is directly added to the vacuum induction furnace in the form of aluminum powder and yttrium oxide powder.

[0032] Comparative Example 2: Different from Example 3 is that B is not added in the form of NiB, but is directly added in the form of boron powder into the vacuum induction furnace.

[0033] Comparative Example 3: Different from Example 3 is that Al, Y2O3 and B are all directly added in the form of powder into the vacuum induction furnace.

[0034] Experimental Example: 1. The products prepared in Examples 1-3 and Comparative Examples 1-3 are subjected to long-term high-temperature high-stress fatigue crack growth rate test, and the steps are as follows: φ20mmx20mm samples are prepared, a mechanical notch (depth 2.5mm, angle 30°) is pre-prepared, and the surface is polished to Ra≤0.2μm; after the sample is clamped and fixed, it is heated to the target temperature (850℃) at a rate of ≤5℃ / min and kept for 1000h, while a constant extrusion pressure of 780MPa is applied to the sample; finally, the sample is taken out, ground and polished, and the main crack length L1(μm) and width W1(μm) are measured under a metallographic microscope.

[0035] 2. The products prepared in Examples 1-3 and Comparative Examples 1-3 are subjected to fatigue crack growth rate test under periodic load, and the steps are as follows: φ20mmx20mm samples are prepared, a mechanical notch (depth 2.5mm, angle 30°) is pre-prepared, and the surface is polished to Ra≤0.2μm; after the sample is clamped and fixed, it is placed in a supercritical water vapor atmosphere (simulating service in a combustion gas environment) at 650℃, and an extrusion pressure of 850MPa is applied to the sample for 5s every 30s; after 1000h of cycling, the sample is taken out, ground and polished, and the main crack length L2(μm) and width W2(μm) are measured under a metallographic microscope.

[0036] The results are shown in the following table: As can be seen from the above table, by passivating aluminum with yttrium oxide, the 650℃ cyclic load crack growth rate of the crack-resistant nickel-based high-temperature alloy is significantly reduced.

[0037] The density of the Ni-B intermediate alloy matches the nickel matrix, enabling uniform dissolution in the liquid phase, and inhibiting the oxidation and volatilization of boron; while boron powder (melting point 2300℃, density about 2.3g / cm 3 ) is easy to float and agglomerate when directly added, and the surface B2O3 impurities generate low-melting-point eutectics (such as Cr-B-O system, melting point <900℃) during smelting, and promote the formation of coarse and brittle borides at the grain boundaries, becoming stress concentration sources. Under the action of load, cracks preferentially initiate and propagate along the brittle borides, leading to intergranular fracture. As can be seen from the above table, the crack growth rate of Comparative Example 2 under 850℃ / 780MPa stress is significantly higher than that of the examples.

[0038] The above embodiments are only illustrative of the principles of the present application and its efficacy, and are not intended to limit the present application. Any modification or change made by any person skilled in the art without departing from the spirit and scope of the present application shall be covered by the claims of the present application.

Claims

1. A crack-resistant nickel-based high-temperature alloy, characterized in that: Calculated by mass percentage, it includes the following components: Cr: 12-18%; Co: 8-15%; Mo: 3-6%; W: 2-4%; Al: 1-3%; Ti: 2-4%; Ru: 0.5-2%; Y: 0.3-1%; B: 0.002-0.01%; the balance is Ni and unavoidable impurities; Among them, Al is passivated by Y2O3; B exists in the form of Ni-B intermediate alloy.

2. A method for preparing the crack-resistant nickel-based high-temperature alloy according to claim 1, characterized in that: The following steps are involved: S1. Pretreatment of aluminum; Aluminum powder and yttrium oxide powder are mixed, sintered under argon protection, and ground to obtain passivated aluminum powder; S2. Preparation of Ni-B master alloy; The nickel oxide powder is immersed in a boron-containing solution and stirred, and then oxidized and dried in air at 250° C. to obtain a pre-coated nickel oxide powder; Boric anhydride powder and pre-coated nickel oxide powder were vacuum dried, sieved and mixed, added with polyvinyl alcohol binder, cold isostatically pressed, and heated under argon protection to generate liquid Ni(BO2)2; Liquid Ni(BO2)2 and carbon powder are pre-reduced at 1350℃ for 30 minutes, and then reacted at 1550-1600℃ to generate NiB; slowly cooled to 1200-1300℃ and kept warm, and inclusions are filtered and intercepted; Casting to obtain NiB master alloy, grinding to obtain NiB master alloy powder; S3. Vacuum induction melting and degassing treatment; Add the dried nickel, chromium, cobalt, molybdenum, tungsten, titanium and ruthenium powders into a vacuum induction furnace, evacuate to vacuum, heat to 1950-2000℃, then cool to 1550-1600℃ for constant temperature melting; introduce high-purity argon gas for degassing; After cooling to 1450-1500℃, add passivated aluminum powder; add Ni-B master alloy powder in batches; The temperature is lowered to 1400-1450℃, the furnace is tilted and poured into a water-cooled copper mold to obtain an ingot; the ingot is cooled under argon protection and then taken out of the furnace; S4. Pulse electroslag remelting; Using an electroslag remelting furnace, preheated and dehydrated ternary slag system CaF2-Al2O3-CaO is loaded into the crystallizer; before smelting, the furnace is evacuated and high-purity argon is introduced, and the crystallizer cooling water system is started simultaneously; the ingot is placed into the molten pool and pulsed intermittently; S5. Cogging forging; The ingot is heated to 1150-1200℃ using a fast forging machine and kept warm, and a multi-directional forging process with alternating axial and radial deformation is adopted, followed by air cooling to room temperature; S6.Cold rolled and cold drawn; After cold rolling, the blank is immediately annealed, and a high-temperature resistant lubricant is evenly sprayed on the surface of the blank. After the lubricating layer solidifies, cold drawing is performed to obtain the finished product; the blank is then placed in an electrolyte for polishing. S7. Heat treatment annealing; After the solution treatment, 1.2 MPa high-pressure nitrogen is introduced to force cool the alloy to 300°C at a rate of 50-100°C / min; an aging treatment is performed, followed by furnace cooling and air cooling to obtain a crack-resistant nickel-based high-temperature alloy.

3. The method for preparing the crack-resistant nickel-based high-temperature alloy according to claim 2, wherein: S1 specifically comprises: mixing aluminum powder and yttrium oxide powder, sintering at 380-400° C. for 1-2 hours under argon protection, and grinding into passivated aluminum powder with a particle size of ≤50 μm.

4. The method for preparing the crack-resistant nickel-based high-temperature alloy according to claim 2, wherein: S2 specifically comprises: completely immersing the nickel oxide powder in a boron-containing solution and stirring, and oxidizing and drying in air at 250° C. to form a Ni-BO coating layer on the surface to obtain a pre-coated nickel oxide powder; The boric anhydride powder and the pre-coated nickel oxide powder were vacuum dried to remove adsorbed water, and sieved to a particle size of ≤50 μm; Mix B2O3 and NiO in a molar ratio of 1:1-1.2, add polyvinyl alcohol binder, cold isostatically press into cylindrical blocks, heat to 950-1000℃ under argon protection, keep warm for 1-1.5h, and react to generate liquid Ni(BO2)2; Liquid Ni(BO2)2 and carbon powder are charged into a vacuum induction furnace at a molar ratio of 1:2.4-2.8 and purged with argon. After pre-reduction at 1350°C for 30 minutes, the mixture is kept at 1550-1600°C for 40-50 minutes to generate NiB by carbothermal reduction reaction. Slowly cool to 1200-1300℃ and keep warm, filter and intercept inclusions; The mixture was poured into a water-cooled copper mold, and the cooling rate was controlled at 50-100°C / s to obtain a NiB master alloy, which was then ground into NiB master alloy powder with a particle size of ≤50μm.

5. The method for preparing the crack-resistant nickel-based high-temperature alloy according to claim 2, wherein: S3 is as follows: the particle size of nickel, chromium, cobalt, molybdenum, tungsten, titanium and ruthenium powders is controlled to 50-150 μm, vacuum dried in advance, and added into the vacuum induction furnace in the order of the bottom layer of high melting point metals W and Mo, the middle layer of Ni, Co and Cr, and the top layer of low melting point metals Ti and Ru. The powders are first pumped with a mechanical pump and then with a molecular pump until the pressure is ≤5×10 -3 Pa, heat up to 1950-2000℃ at a rate of 10-15℃ / min, keep warm for 30-40min to completely dissolve the refractory metal, cool down to 1550-1600℃, and melt at constant temperature for 2-2.5h; High-purity argon is introduced at a flow rate of 5-10 L / min and degassing is performed at 50-80 Pa for 20-30 minutes; After cooling to 1450-1500℃, add passivated aluminum powder through the secondary feeding device in the vacuum chamber; add Ni-B master alloy powder in 2-3 times, with an interval of 3-5 minutes between each addition; The temperature is lowered to 1400-1450°C, the furnace is tilted and poured into a water-cooled copper mold to obtain an ingot at a pouring speed of 3-5 kg / min; the ingot is cooled under argon protection and then taken out of the furnace.

6. The method for preparing the crack-resistant nickel-based high-temperature alloy according to claim 2, wherein: S4 is specifically as follows: using an electric slag remelting furnace, preheating and dehydrating the ternary slag system CaF2-Al2O3-CaO to make the slag moisture content ≤0.05%, and then loading it into the crystallizer; before smelting, evacuate the furnace body to ≤10Pa, and then continuously introduce high-purity argon gas to the furnace until the oxygen content is ≤50ppm, and simultaneously start the crystallizer cooling water system to maintain the cooling water inlet and outlet temperature difference ≤5℃ to prevent local overheating; put the ingot into the molten pool, control the voltage to 40-50V, the current to 2000-3000A, and intermittent pulse.

7. The method for preparing the crack-resistant nickel-based high-temperature alloy according to claim 2, wherein: S5 is specifically as follows: the ingot is heated to 1150-1200℃ by a fast forging machine and kept warm for 1.5-2h, a multi-directional forging process with alternating axial and radial deformation is adopted, the final forging temperature is 900-950℃, and then air-cooled to room temperature.

8. The method for preparing the crack-resistant nickel-based high-temperature alloy according to claim 2, wherein: S6 specifically involves the coordinated operation of a two-roll cold rolling mill and a chain cold drawing mill, with cold rolling followed by cold drawing. After cold rolling, the billet is immediately transferred to an argon-protected annealing furnace, kept at 750-800°C, slowly cooled at a rate of ≤30°C / min, and then air-cooled. A high-temperature resistant lubricant is evenly sprayed on the billet surface to a thickness of 5-10 μm. After the lubricating layer solidifies, cold drawing is performed to obtain the finished product. Polishing treatment in electrolyte.

9. The method for preparing the crack-resistant nickel-based high-temperature alloy according to claim 2, wherein: S7 is specifically as follows: solution treatment is carried out in a box-type vacuum furnace at 1080-1120°C in an argon atmosphere; after the solution treatment is completed, 1.2MPa high-pressure nitrogen is introduced at a rate of 50-100°C / min to force cooling to 300°C; the temperature is raised to 750-800°C for aging treatment, and then air-cooling is performed after furnace cooling to obtain a crack-resistant nickel-based high-temperature alloy.

10. Use of the crack-resistant nickel-based high-temperature alloy according to claim 1 in preparing hot-end components of aircraft engines or gas turbines.

Citation Information

Patent Citations

  • High-performance easy-to-process nickel-based deformation high-temperature alloy and preparation method thereof

    CN110551920A

  • Nickel-based high-temperature alloy wire and preparation method thereof

    CN117684046A

  • Production of high-temperature nickel-based composite

    RU2563084C1

  • Intermetallide matrix based metal-ceramic composite material and its production method

    RU2686831C1

Cited By

  • High-strength high-temperature-resistant alloy material for gas turbine casing and preparation method thereof

    CN121087399A